THE IMPORTANCE OF IXLA (IMMUNOLUMINESCENT AUTOMATIC ANALYZER) IN LABORATORY DIAGNOSTICS - Najmiddinova Nigora Kamoliddinovna; Shakarova Dilshoda Omon qizi; Sayitova Madina Dostonboyevna (Ustozlar uchun, 2025)
Annotation. IXLA (Immunoluminescent Automatic Analyzer) is a modern diagnostic device that utilizes immunoluminescence methods for highly accurate and automated analysis of biological samples. This analyzer is widely used in laboratory diagnostics for detecting hormones, tumor markers, infectious diseases, and other biomarkers. The key advantages of IXLA include high sensitivity, precision, fast processing time, and minimal operator intervention. This equipment significantly enhances the efficiency of medical diagnostics and provides reliable results for large-scale laboratory testing..